Assessing Program Satisfaction and Employment Outcomes Among Bachelor of Science in Information Technology Graduates of Notre Dame of Jolo College - Edgar Jansol Acevedo; Marcilyn Lee Matriz (European Scientific Journal, ESJ, 2025)
The study assessed BSIT graduates' program satisfaction, employment outcomes, and the usefulness of their academic program for employment. It also examined factors influencing school and program selection, institutional values, and employment aspects such as status, sector, salary, wait time, and position. Program satisfaction was measured across teaching, learning, study conditions, guidance, competency attainment, and employment readiness. It further explored whether employment readiness, institutional values, and employment status predict program satisfaction. A sample of 58 respondents participated in a survey, selected through stratified sampling from a population of 111. Data were analyzed using descriptive statistics and multiple regression. Results showed that holistic education influenced school selection, while program choice was shaped by resources and qualified faculty. The employment rate was 66%, with 61% working in the government sector. Among the employed, 50% found jobs within six months, 63% held non-permanent roles, 39% earned below the median salary, and 87% held rank-and-file positions. Graduates reported the highest satisfaction in teamwork-based teaching, respectful interaction, modern learning tools, and hands-on training. They found problem analysis skills useful for employment and identified God-fearing and respect as core institutional values. Regression analysis indicated that employment readiness and being employed significantly predicted program satisfaction. Graduates confirmed the program’s relevance to their employment and growth. Those who were work-ready and employed reported greater satisfaction. While values like being God-fearing and respectful were appreciated, they had minimal impact on program satisfaction. The study recommended integrating hands-on training, job-readiness modules, and career guidance into the BSIT curriculum, and aligning program content with industry needs through regular stakeholder input.